Water Well Management: A Proactive Maintenance Program Pays Off. Issue 3 (5th March 2019) - Judkins, Michael; Kennison, Michael
Abstract : "Run to failure" is a costly approach to well maintenance and rehabilitation. Shifting to a proactive maintenance strategy can extend pump and well service life, save money, and keep water quality consistent.